Comorbidity of atopic dermatitis and diseases of the gastrointestinal tract - A. D. Bogomazov; O. V. Pratsko (Лечащий Врач, 2024)
Background. One of the most common early manifestations of allergic pathology in childhood is atopic dermatitis. Having a comprehensive impact on the child’s body, the disease leads to a significant decrease in the quality of his life, as a result of which this nosology represents a serious public health problem. Currently, many researchers consider the gastrointestinal tract as a target organ for atopic dermatitis, since a significant part of all complaints from patients with atopic dermatitis are gastrointestinal. On the other hand, the development of diseases of the gastrointestinal tract, especially in early childhood in the presence of a burdened allergic history in the child’s relatives, increases the likelihood of the formation of atopic dermatitis or acts as a risk factor for the transition of an existing disease to severe or moderate forms, as well as increased frequency of exacerbations.Objective. The aim is to study and analyze the relationship between the pathogenesis of atopic dermatitis and gastrointestinal diseases in children of different ages.Materials and methods. The object of the study is 436 outpatient records of patients in the allergy department of the regional children's clinical hospital of the Kursk Region Health Committee. Among the patients, 238 were female and 198 were male, in the age category from 1 month to 16 years. During the research, the following was used: copying data from outpatient records, analysis of scientific literature, statistical data processing was carried out using Excel, Statistika 10 programs. Results. From the data obtained it follows that both the presence of pathological changes in the gastrointestinal tract system is a risk factor for the development of atopic dermatitis or the worsening of its course, and the presence of the development of blood pressure leads to a decrease in the efficiency of the tissues and organs of the gastrointestinal tract, since in both In this case, there is an increase in the allergic load on the body, damaging tissues and organs. In this connection, we can conclude about the relationship between atopic dermatitis and diseases of the gastrointestinal tract.Conclusion. Due to the presence of comorbidity between atopic dermatitis and gastrointestinal pathology, it is necessary to pay close attention to the diagnosis of gastrointestinal disorders in children with a clinical diagnosis of atopic dermatitis and prevent their development in the early stages.